Farmers' perceptions and assessment of cattle traits in periurban dairy systems of Bobo-Dioulasso (Burkina Faso) - Hamadou, S.; Kamuanga, M. (2004)
This study was conducted to identify the 6 major criteria that periurban dairy producers of the subhumid zone of Burkina Faso use in upstream decisions on breed composition of their herds through the repertory grid method. This study was carried out in a sample of 283 producers of Bobo-Dioulasso, of which 8.4% engaged in market-oriented production systems. Milk yield, precocity, fecundity, capacity of the animal to graze various categories of grass and support thirst during dry season, disease resistance and mobility were identified as the main selection criteria for dairy cows. Fitness to traction, feeding ease, virility, disease resistance, size and mobility were important criteria in bull selection. Only crossbreds between zebu (Bos indicus) and taurine (Bos taurus), humpless trypanotolerant cattle were shown to possess all the required traits of a dairy herd. With the introduction of improved management methods, there was a tendency to disfavour the humpless, trypanotolerant breeds inspite of their great adaptability to the subhumid environment. There was a need to implement enabling policies that would help smallholder dairy producers to invest in modern technology for intensification of milk production in order to meet the increasing demand for milk. This could be accomplished while preserving the breeds under threat of extinction.